2021
DOI: 10.1038/s41598-021-86505-7
|View full text |Cite
|
Sign up to set email alerts
|

Free-water diffusion tensor imaging improves the accuracy and sensitivity of white matter analysis in Alzheimer’s disease

Abstract: Magnetic resonance imaging (MRI) based diffusion tensor imaging (DTI) can assess white matter (WM) integrity through several metrics, such as fractional anisotropy (FA), axial/radial diffusivities (AxD/RD), and mode of anisotropy (MA). Standard DTI is susceptible to the effects of extracellular free water (FW), which can be removed using an advanced free-water DTI (FW-DTI) model. The purpose of this study was to compare standard and FW-DTI metrics in the context of Alzheimer’s disease (AD). Data were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
59
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 61 publications
(49 reference statements)
11
59
0
1
Order By: Relevance
“…In diffusion tensor imaging (DTI) modeling of dMRI data, fractional anisotropy (FA) reflects an ellipsoid shape of diffusivity within a given voxel. Higher FA values are thought to arise from higher diffusivity along one preferred direction (i.e., along intact myelinated fibers, thus representing fiber integrity) or from a loss of crossing fibers [11][12][13] . On the other hand, mean diffusivity (MD) represents the magnitude of diffusion (average of eigenvalues) regardless of the directionality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In diffusion tensor imaging (DTI) modeling of dMRI data, fractional anisotropy (FA) reflects an ellipsoid shape of diffusivity within a given voxel. Higher FA values are thought to arise from higher diffusivity along one preferred direction (i.e., along intact myelinated fibers, thus representing fiber integrity) or from a loss of crossing fibers [11][12][13] . On the other hand, mean diffusivity (MD) represents the magnitude of diffusion (average of eigenvalues) regardless of the directionality.…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that this WM-cortex PET correlation may be partly due to an additive off-target signal within the cortex, which may explain the improved stability of longitudinal PET in AD target regions using white matter as a reference region 53 . Apart from the WM-cortex correlation in PET signal, the relationship between lower 18 F-AV45 SUVR and higher FW-adjusted FA may also be explained by a loss of crossing fibers typically resulting in higher FA and FW-adjusted FA 11,13,54 . For example, Douaud et al 12 showed that the only region where DTI metrics were significantly different between healthy controls and MCI was an area of crossing fibers in the centrum semiovale; here, the motor-related projection fibers that crossed the degenerating fibers were selectively preserved, resulting in an increased FA in MCI.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of this study regards the diffusion-weighted image acquisition protocol. Recent work has shown that free-water correction improves the accuracy and sensitivity of white matter analyses (59,60) by fitting a bi-tensor model to each voxel to account for partial volume effects (i.e., voxels that contain brain tissue and free-water such as cerebrospinal fluid); however, it is advised to apply this technique to single-shell diffusion-weighted images that were acquired with b-values less than 1000 s/mm 2 (61). Our data were acquired with b-value = 2500 s/mm 2 , therefore we were unable to apply free-water correction due to our imaging acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…Free-water corrected DTI maps were calculated using an in-house MATLAB script (Fig. S1 ) 20 , 29 . Finally, we acquired the mean of the diffusion measures of each periependymal lining shell.…”
Section: Methodsmentioning
confidence: 99%
“…Further, it is important to correct for partial volume effect in the voxels surrounding ventricles because contamination of CSF has a large effect on DTI parameters. To overcome the effect of extracellular free-water on DTI metrics, we adopted a free-water correction algorithm that quantify and remove the contribution of extracellular free-water 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%